Pemanfaatan Minyak Jelantah dan Tanaman Serai Sebagai Lilin Aromaterapi Ramah Lingkungan untuk Meningkatkan UMKM di Desa Battu Winangun (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Used cooking oil is a household waste that is often disposed of carelessly, potentially polluting the environment and endangering health. In Battu Winagun Village, the availability of used cooking oil from household activities and the abundant potential of lemongrass plants have not been optimally utilized. This community service activity aims to increase the community's knowledge and skills in processing used cooking oil and lemongrass plants into environmentally friendly products with economic value, namely natural aromatherapy candles. The implementation method includes socialization of the negative impacts of used cooking oil on the environment, training in the process of filtering and processing used cooking oil, extracting lemongrass aroma, and assistance in making and packaging aromatherapy candles. The results of the activity showed that the Battu Winagun Village community was able to understand the importance of managing used cooking oil waste and utilizing lemongrass plants as a natural additive. This activity has an impact on reducing environmental pollution and opening up creative business opportunities based on the village's local potential. Thus, the use of used cooking oil and lemongrass plants can be a sustainable solution in waste management while improving the economy of the Battu Winagun Village community.